PENGARUH HARGA DAN KEGIATAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA PT. CAHAYA ELECTRIC DI TANGERANG - Udin Ahidin (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study aims to determine the effect of prices and promotional activities on Consumer satisfaction at PT. Cahaya Electric in Tangerang. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study have a significant effect on consumer satisfaction by 43.9%, the hypothesis test obtained t count t table or (8.580 1.986). Promotional activities significantly influence Consumer satisfaction by 45.1%, the hypothesis test obtained t count t table or (8.603 1.986). Price and promotion activities simultaneously have a significant effect on customer satisfaction by 54.9%, the hypothesis test is obtained F count F table or (56,651 2,700).